The History of Clinical Psychology in Greece: A Brief Review – Legal Deficiencies, Practical Dimensions and Challenges for the Future - Katerina Flora (Clinical Psychology in Europe)
[Background] The history of clinical psychology in Greece spans more than 150 years. However, this branch of psychology concerned with the assessment and treatment of mental illness and psychological problems has not yet acquired the institutional and general recognition to which it is entitled. [Aims] This article intends to highlight, chronologically, the basic elements of the history of clinical psychology in Greece, beginning with the important contribution of the work of philologist Panagiota Kazolea-Tavoularis. [Results] From the first references in the context of medical studies during the 19th century, clinical psychology gradually develops through its application in pedagogical, laboratory, and clinical contexts to become an independent discipline alongside the consolidation of general psychology. Special mention is made of the scientists who pioneered this direction. [Conclusion] The present review highlights historical milestones and concludes with the current situation, in which important steps have been taken. However, significant changes are needed at the institutional level.